Historical Dictionary of Science Fiction Cinema - Booker, M. Keith (Rowman & Littlefield Publishers, 2020)
In the years since Georges Méliès’s Le voyage dans la lune (A Trip to the Moon) was released in 1902, more than 1000 science fiction films have been made by filmmakers around the world. The versatility of science fiction cinema has allowed it to expand into a variety of different markets, appealing to age groups from small children to adults. The technical advances in filmmaking technology have enabled a new sophistication in visual effects. This second edition of Historical Dictionary of Science Fiction Cinema contains a chronology, an introduction, and an extensive bibliography. The dictionary section has over 400 cross-referenced entries on important personalities, films, companies, techniques, themes, and subgenres. This book is an excellent resource for students, researchers, and anyone wanting to know more about science fiction cinema.